Comparative analysis of Naja kaouthia venom from North-East India and Bangladesh and its cross reactivity with Indian polyvalent antivenoms. (June 2019) - Deka, Archana; Reza, Md Abu; Faisal Hoque, Kazi Md; Deka, Kamalakshi; Saha, Sougata; Doley, Robin
Abstract: Naja kaouthia is one of the most prevalent medically important snakes of North East India and Bangladesh responsible for most of the bite cases. In this study, an attempt was made to decipher venom variation of Naja kaouthia venom from North East India and Bangladesh. Using multidimensional methods including reverse phase HPLC, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1D-PAGE) and two-dimensional gel electrophoresis (2D-PAGE), the quantitative differences in venom composition have been revealed. Moreover, tested in-vitro biochemical and biological activities also exhibited differences which could be due to venom variability. Furthermore, neutralization efficacy of commercially available Indian polyvalent antivenoms (Vins, Bharat Serum, Haffkine) was evaluated and the results displayed significant differences in neutralizing efficacy between the antivenoms. Immunoblotting experiments showed antivenom molecules cross reacted with high molecular mass components while poorly reacted towards low molecular mass proteins. Immuno-depletion study demonstrated that Vins polyvalent antivenom was poor in immunocapturing the venom proteins of both North East Indian and Bangladesh origin Naja kaouthia at the ratio of 1:16 (venom: antivenom). Graphical abstract: Image 1 Highlights: North East Indian and Bangladesh origin Naja kaouthia venom demonstrates variation. Neutralization of venom toxic effects was analysed using three Indian polyvalent antivenoms. Haffkeine polyvalent antivenom performed better in neutralizing toxic effects compared to Vins and Bharat Serum. Antivenomics study revealed poor immunocapturing ability of Naja kaouthia venom proteins by Vins polyvalent antivenom.